A pressurized high-flux solar reactor for the efficient thermochemical gasification of carbonaceous feedstock. (1st April 2017) - Müller, F.; Poživil, P.; van Eyk, P.J.; Villarrazo, A.; Haueter, P.; Wieckert, C.; Nathan, G.J.; Steinfeld, A.
Highlights: 3-kW solar reactor was experimentally demonstrated with concentrated radiation. Charcoal-water slurry was converted to high-quality pressurized syngas. Reaction extent of 94% was obtained in less than 5 s. The solar-to-fuel energy conversion efficiency reached 20%. The calorific value of the feedstock was solar upgraded by 35%. Abstract: We report on the design and first-ever experimental demonstration of a 3 kW pressurized solar reactor for thermochemically converting carbonaceous feedstocks into gaseous fuels. It uses a windowless SiC cavity to efficiently absorb and transfer concentrated solar radiation to an annular gas-particle vortex flow created by injecting tangentially a charcoal/water slurry at high pressures. Experiments were carried out in a high-flux solar simulator under a solar concentration ratio equivalent to 3718 suns. For slurry feeding rates in the range 0.42–1.26 g/min, H2 O:C molar ratios in the range 1.48–1.98, and absolute reactor pressures in the range 1–6 bar, the nominal reactor temperature was between 1009 and 1273 °C yielding high-quality syngas with a carbon conversion up to 94% within residence times of less than 5 s. The peak solar-to-fuel energy conversion efficiency, defined as the ratio of the heating value of the syngas produced to the solar radiative energy input plus the heating value of the slurry converted, reached 20%. The calorific value of the feedstock was solar upgraded by 35%, thus outperforming autothermal gasification in addition to delivering higher syngas output per unit of feedstock and eliminating the need for upstream air separation. The performance of this robust windowless design also was compared with that of an equivalent windowed configuration in which the gas-particle vortex flow was directly exposed to high-flux solar irradiation.